2019
DOI: 10.15210/lepaarq.v16i32.16387
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Colonial Groups From Brazilian Coast and Sharks: First Glimpse on a Complex Relationship Through the Case Study of the Shallow Site Rio Do Meio, Santa Catarina

Abstract: The excavation of the coastal shallow site Rio do Meio (500-700 years cal BP, Santa Catarina, Brazil) made available a large faunal collection with a particularly interesting frequency of shark remains. Considering all the identified faunal fragments, the centra and teeth of sharks participate with 15% of the remains, being the third most important element behind the bones of fish and shells. The high frequency of shark remains led to the questioning of the dietary value of this resource for coastal groups, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…As poucas publicações sobre a indústria baseada em material faunístico trazem dados importantes sobre quais animais tiveram ossos, dentes ou conchas selecionados para servir de matéria-prima e indícios sobre sua área de captação, possibilidade do uso de adornos como marcadores de identidade e importância de algumas espécies para manufatura de parafernália funerária (e.g. GILSON;LESSA, 2019;KLOKLER, 2014;SALADINO, 2017). A imensa maioria da indústria arqueofaunística foi recuperada em contextos funerários, ocorrendo eventualmente também em camadas construtivas.…”
Section: Tecnologiaunclassified
“…As poucas publicações sobre a indústria baseada em material faunístico trazem dados importantes sobre quais animais tiveram ossos, dentes ou conchas selecionados para servir de matéria-prima e indícios sobre sua área de captação, possibilidade do uso de adornos como marcadores de identidade e importância de algumas espécies para manufatura de parafernália funerária (e.g. GILSON;LESSA, 2019;KLOKLER, 2014;SALADINO, 2017). A imensa maioria da indústria arqueofaunística foi recuperada em contextos funerários, ocorrendo eventualmente também em camadas construtivas.…”
Section: Tecnologiaunclassified
“…The three criteria that characterize the Rio do Meio site as a shallow site with ceramics are (1) its physiographic position directly on a beach, (2) the presence of Itararé ceramics, and (3) its chronological bracket between 500 and 700 years cal BP (Gilson and Lessa 2020). No traces of burials have yet been revealed (Gilson and Lessa 2019b, 2021a), which makes the Rio do Meio site unique among other shallow sites on Santa Catarina Island and the southern Brazilian coast, where burials are common.…”
Section: Archaeological Contextmentioning
confidence: 99%
“…Lopes et al. (2016) identified 26 shark and ray taxa to genus and species level from teeth, vertebrae and tail spines from shell mounds dating between about 3000 BC and AD 500 in south east Brazil, where many shark teeth were drilled as ornaments, tools or weapons, and Gilson and Lessa (2019, 2021) similarly identified 15 taxa to genus and species level for southern Brazil where tols use was also recorded. Desse and Du Buit (1971) have shown that shark and ray can be identified to low taxonomic levels using radiographs of vertebrae, and Gobalet (1990) identified shark to species level using this method at pre‐Columbian coastal sites in California.…”
Section: Sharks and Rays In Archaeological Analysismentioning
confidence: 99%